House Price Expectations and Housing Choice - Jochen Mankart; Alexander Ludwig; Mirko Wiederholt; Jorge Quintana; Nathanael Vellekoop (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
What is the role of heterogenous house-price expectations for boom-bust cycles in the housing market? We exploit a unique Dutch panel data set on households' house price expectations and their consumption, savings and housing choices for the period 2003-2016. This period was characterized by a pronounced boom-bust cycle in the housing market. Conditioning the sample on household heads who report non-zero house price expectations, we find that expectations closely track realized house prices. We next develop a structural life-cycle model of the Dutch housing market where we distinguish household types according to their house price expectations. We employ a calibrated model variant to test if observed variations in expectations can account for the housing boom-bust cycle. First results show that our model closely matches the observed fluctuations of the rent-to-price ratio in the data but overshoots the size of the housing boom.
Keywords: D14; D84; D31; E21; E30; G21; R21; 330; Housing; survey expectations; house price cycles; life-cycle model